Mass Media in Creating Awareness Among Agricultural Labours During COVID-19 Pandemic in Birbhum, West Bengal (Indian Journal of Extension Education, 2021)
In the crisis period due to global health threat caused by COVID-19 pandemic in the last few months of 2020 and the imposed lockdown in India, mass media played a very crucial role to make the countless mass of recipients aware and conscious about what is happening throughout the world. The study aims to find out informative role of mass media over traditional media in creating awareness about agriculture during the pandemic and exposure to mass media by the Santals of Birbhum District, West Bengal. Telephonic questionnaire through mobile contact was applied to collect quantitative data from 100 Santal agricultural labours of both local and migrant (50 male, 50 female) from 4 selected villages. It was observed that, though availability of mass media with the Santals was limited, however, their accessibility to mass media like TV or mobile phone was found somewhat better in creating awareness and consciousness about agricultural activities during the pandemic period among the Santals. Mean value of agricultural information consumption based on mass media of female Santals (X2= 109.43) was better than the male Santals (X1= 106.18). ‘t’ value, which was 3.40, much more than the significant level, indicated that the agricultural information consumption based on mass media of female Santals is greater than that of male Santals in COVID-19 pandemic. Study finally suggested for balanced combination of traditional media and mass media in developing more awareness and consciousness among the Santals in the epidemic and pandemic period.